The Mammalian Circadian Clock Protein Period Counteracts Cryptochrome in Phosphorylation Dynamics of Circadian Locomotor Output Cycles Kaput (CLOCK) - Matsumura, Ritsuko (J Biol Chem, 2014)
The circadian transcription factor CLOCK exhibits a circadian oscillation in its phosphorylation levels. Although it remains unclear whether this phosphorylation contributes to circadian rhythm generation, it has been suggested to be involved in transcriptional activity, intracellular localization, and degradative turnover of CLOCK. Here, we obtained direct evidence that CLOCK phosphorylation may be essential for autonomous circadian oscillation in clock gene expression. Importantly, we found that the circadian transcriptional repressors Cryptochrome (CRY) and Period (PER) showed an opposite effect on CLOCK phosphorylation; CRY impaired BMAL1-dependent CLOCK phosphorylation, whereas PER protected the phosphorylation against CRY. Interestingly, unlike PER1 and PER2, PER3 did not exert a protective action, which correlates with the phenotypic differences among mice lacking the Per genes. Further studies on the regulatory mechanism of CLOCK phosphorylation would thus lead to elucidation of the mechanism of CRY-mediated transcriptional repression and an understanding of the true role of PER in the negative feedback system.